MODISS as a Differentiated Learning Support to Improve Student Learning Outcomes - Anwaril Huda; Novvia Puspita (Journal of Advances in Physics Education, 2025)
This study aims to develop MODISS (Interactive Digital Module for Integrated Social-Emotional Learning) as a supporting media for differentiated learning strategies to enhance student learning outcomes. MODISS is an offline interactive media featuring videos, animations, interactive buttons, and interactive assessments. The offline operation of MODISS is designed to accommodate schools located in areas with limited signal access and minimize data usage for students. This innovation employs the ADDIE model of research and development, which consists of five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The analysis and development of MODISS were conducted at SMPN 3 Pesawaran and SMPN Satap 5 Pesawaran. MODISS was designed using MS Office PowerPoint, Canva, ISpring, and Website 2 APK Builder v.5.1.0.1, and subsequently validated by practitioners. Prior to development, MODISS underwent readability and usability testing, yielding excellent results. It also underwent field trials to assess its practicality, which demonstrated a very practical outcome. Based on the assessment analysis, significant improvements in student learning outcomes were observed after the use of MODISS.